2018
DOI: 10.1103/physreva.97.052503
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Pauli constraints in small atoms

Abstract: The natural occupation numbers of fermionic systems are subject to non-trivial constraints, which include and extend the original Pauli principle. A recent mathematical breakthrough has clarified their mathematical structure and has opened up the possibility of a systematic analysis. Early investigations have found evidence that these constraints are exactly saturated in several physically relevant systems; e.g. in a certain electronic state of the Beryllium atom. It has been suggested that in such cases, the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…The pure-state N -representability conditions of the 1-RDM, also known as the generalized Pauli constraints [47][48][49][51][52][53][54][55][56][57][58], are in the form of linear inequalities on the set of 1-RDM eigenvalues (natural occupation numbers) for a given number of electrons and orbitals. In 1972 Borland and Dennis [47] discovered these constraints that extend the Pauli exclusion principle in the case of 3 electrons in 6 orbitals, and in 2006 Klyachko (and in 2008 with Altunbulak) generalized their derivation for potentially arbitrary numbers of electrons and orbitals [52,53].…”
Section: A Quantum-classical Hybrid Algorithm With N -Representabilimentioning
confidence: 99%
See 1 more Smart Citation
“…The pure-state N -representability conditions of the 1-RDM, also known as the generalized Pauli constraints [47][48][49][51][52][53][54][55][56][57][58], are in the form of linear inequalities on the set of 1-RDM eigenvalues (natural occupation numbers) for a given number of electrons and orbitals. In 1972 Borland and Dennis [47] discovered these constraints that extend the Pauli exclusion principle in the case of 3 electrons in 6 orbitals, and in 2006 Klyachko (and in 2008 with Altunbulak) generalized their derivation for potentially arbitrary numbers of electrons and orbitals [52,53].…”
Section: A Quantum-classical Hybrid Algorithm With N -Representabilimentioning
confidence: 99%
“…We implement an algorithm for 3-electron molecules in open-shell, doublet states with significant strong electron correlation. A pure-state N -representability condition, known as a generalized Pauli constraint, which was originally discovered by Borland and Dennis at IBM in a series of computations on a classical computer [47], allows us to express the N -representable 2-RDM for three-electron systems as a functional of only the 1-RDM [48,49]. We optimize the eigenvalues of the 1-RDM on the quantum computer and its eigenfunctions, which are not restricted by N -representability, on the classical computer.…”
Section: Introductionmentioning
confidence: 99%
“…The motivation for proposing such generalizations of CASSCF ansatzes is twofold. On the one hand, the study of smaller atoms [45] has revealed that the GPCs have an additional significance for ground states beyond the one of the Pauli exclusion principle constraints, as quantified by the Q-parameter [14]. On the other hand, not all configurations i within a complete active space are relevant and it would be preferable to identify only the most significant ones.…”
Section: Implications Of Degenerate Pinned Occupation Numbersmentioning
confidence: 99%
“…Recently, it has been suggested that the generalized Pauli constraints may facilitate the development of more accurate functionals within density-matrix functional theory [41][42][43] . Since quasipinning (say, D j (n) ≈ 0) is approximately observed for several ground states, the quasipinning "mechanism" has attracted some attention in quantum chemistry and quantum-information theory [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] .…”
Section: Robustness Of Fermionic Constraintsmentioning
confidence: 99%